Strategy for the Construction of SARS-CoV-2 S and N Recombinant Proteins and Their Immunogenicity Evaluation - Paulo Henrique Guilherme Borges; Barbara Gregio; Helena Tiemi Suzukawa; Gislaine Silva-Rodrigues; Emanuella de Castro Andreassa; Isabela Madeira de Castro; Guilherme Bartolomeu-Gonçalves; Emerson José Venancio; Phileno Pinge-Filho; Viviane Monteiro Góes; Celso Vataru Nakamura; Eliandro Reis Tavares; et al. (BioTech, 2025)
This study reports the construction, expression, and purification of synthetic SARS-CoV-2 spike (S) and nucleoprotein (N) containing immunodominant epitopes. The pET28aS_epit construct included epitopes 287–317, 402, 507, 524–598, and 601–640, while the pET28aN_epit construct included residues 42–62, 153–172, and 355–401. Commercial sequences of both proteins were used as controls. The four constructs were expressed using the Escherichia coli BL21(DE3) star strain at 37 °C. The results show that the S protein constructs were insoluble, unlike the N protein constructs. Both recombinant proteins induced immune responses in mice and were recognized by antibodies present in sera from COVID-19-positive and/or SARS-CoV-2-vaccinated humans. No significant differences in immune recognition were observed between our constructs and the commercially available proteins. In conclusion, S_epit and N_epit could be promising starting points for the development of new strategies based on immunological reactions for the control of SARS-CoV-2 infections.